2014
DOI: 10.1021/am404769z
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous Cobalt Hydroxide with Superior Pseudocapacitive Performance

Abstract: Cobalt hydroxide (Co(OH)2) has received extensive attention for its exceptional splendid electrical properties as a promising supercapacitor electrode material. Co(OH)2 study so far prefers to crystal instead of amorphous, in spite of amorphous impressive electrochemical properties including the ability to improve the electrochemical efficiency based on the disorder structure. The amorphous Co(OH)2 nanostructures with excellent electrochemical behaviors were successfully synthesized by a simple and green elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
115
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(124 citation statements)
references
References 30 publications
9
115
0
Order By: Relevance
“…[ 21,22 ] However, the ternary amorphous phase exhibits the best long-term cycling stability among all amorphous metal hydroxides in our studies. Therefore, these experimental results suggest that an amorphous phase with mixed metals seems to be good for the longterm cycling stability.…”
Section: Wileyonlinelibrarycommentioning
confidence: 74%
See 1 more Smart Citation
“…[ 21,22 ] However, the ternary amorphous phase exhibits the best long-term cycling stability among all amorphous metal hydroxides in our studies. Therefore, these experimental results suggest that an amorphous phase with mixed metals seems to be good for the longterm cycling stability.…”
Section: Wileyonlinelibrarycommentioning
confidence: 74%
“…It has been shown that the integrated electrochemical performance of amorphous metal hydroxides, such as Ni(OH) 2 and Co(OH) 2 , is commensurate with the crystallinity of the materials in the supercapacitor. [ 21,22 ] Considering the excellent electrochemical performance of crystalline mixed-metal hydroxide electrodes several benefi ts should be realizable by the development of amorphous mixed-metal hydroxide electrodes. However, commonly used methods for the production of amorphous oxide materials are not typically amenable to amorphous mixed-metal hydroxides.…”
mentioning
confidence: 99%
“…The reaction process was facile and efficient, simply involving heating the reactants under reflux in ethylene glycol for 1 h. Yang and colleagues [76][77][78] have also contributed to the synthesis of amorphous hydroxide materials by preparing flower-like spherical nanostructures using a unique electrochemical technique that is simple, green and inexpensive. These spheres and hollow structures are interesting candidates for use in energy storage [94].…”
Section: Science China Materialsmentioning
confidence: 99%
“…The large number of under-coordinated atoms (good electron acceptors) and reactive sites at the surface means that amorphous materials also have the advantage over crystalline ones in their contact with the electrolyte and active substances (electron donors), which favors electrochemical processes. In regard to the merits discussed above, amorphous nanomaterials have already demonstrated their superior performance over bulk crystalline materials in various electrochemical applications, including lithium-and/or sodium-ion batteries [51,62,66,71,79,84,[96][97][98][99][100], super-or pseudo-capacitors [77,78,83], electrochemical water splitting [59] and sensors [72,81]. The amorphous CoSnO 3 @C nanoboxes reported by Wang et al [79] showed high initial discharge and charge capacities of around 1,410 and 480 mA h g −1 , respectively, as revealed in Fig.…”
Section: Applications Electrochemical Electrode Materialsmentioning
confidence: 99%
See 1 more Smart Citation